2015
DOI: 10.1039/c5cp00285k
|View full text |Cite
|
Sign up to set email alerts
|

Modular construction of size-selected multiple-core Pt–TiO2 nanoclusters for electro-catalysis

Abstract: Size-selected binary platinum-titanium dioxide (Pt-TiO2) clusters have been generated using a magnetron sputtering gas condensation cluster source and imaged using a Scanning Transmission Electron Microscope (STEM) in High Angle Annular Dark Field (HAADF) mode. The core-shell clusters exhibit a Pt core of preferred size 30 ± 6 atoms (1 nm), embedded in an oxidised Ti shell, independent of the overall cluster size (varied between 2 nm and 5 nm). Smaller clusters, with mass ≤50 000 Daltons, show a single Pt core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The grayscale areas have been shown to be composed by a TiO 2 matrix [24] related to the lower Z numbers of the components (Z Ti = 22, Z O = 8). The Ag NPs are partially encapsulated, more similar to the Janus-like than the core-shell configuration [28], the former being commonly observed for bimetallic noble metal nanoparticles [29]. Previous investigations about the structure of the oxide matrix performed by X-ray diffraction [24] suggested that the TiO 2 is amorphous, in agreement with the TEM image shown in Figure 1d, where no sign of regular atomic arrangement can be observed in the “gray” areas.…”
Section: Resultsmentioning
confidence: 99%
“…The grayscale areas have been shown to be composed by a TiO 2 matrix [24] related to the lower Z numbers of the components (Z Ti = 22, Z O = 8). The Ag NPs are partially encapsulated, more similar to the Janus-like than the core-shell configuration [28], the former being commonly observed for bimetallic noble metal nanoparticles [29]. Previous investigations about the structure of the oxide matrix performed by X-ray diffraction [24] suggested that the TiO 2 is amorphous, in agreement with the TEM image shown in Figure 1d, where no sign of regular atomic arrangement can be observed in the “gray” areas.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were prepared in the University of Birmingham (BHAM) [10]. The core-shell nanoparticles were produced using a specialized magnetron sputtering technique [32] with 75 % titanium and 25 % platinum by weight in the sputtering target, corresponding to 13 Ti atoms for every Pt atom.…”
Section: Monodispersed Nanoparticle Samplesmentioning
confidence: 99%
“…The commonly used method for the characterization of such "atomic clusters" is the analysis of scanning transmission electron microscope (STEM) images [9]. For the specific Pt-Ti nanoparticle, this method has been used before to identify the Pt atoms and calculate the number of atoms from the determined volume of a Pt sphere [10]. The stability and catalytic properties of nanoparticles may be improved by combing two or more metallic elements [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As an earth‐abundant and environment‐friendly material, TiO 2 can be served as good photocatalyst or photo‐electro‐catalyst ,,,. However, it is not a good electrocatalyst for OER due to a corresponding high overpotential.…”
Section: Introductionmentioning
confidence: 99%